2011
DOI: 10.5463/dcid.v22i1.18
|View full text |Cite
|
Sign up to set email alerts
|

Rehabilitation Services for Persons Affected by Stroke in Jordan

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 18 publications
0
18
0
Order By: Relevance
“…Such factors have been previously identified in different contexts. For example, alternative explanatory processes of stroke and its recovery have been identified in non-Western communities [ 29–32 ], and poor stroke knowledge in minority ethnic groups is a common research finding [ 33–35 ]. Furthermore, it has been suggested that differences in recovery concepts based on cultural understandings may influence the therapeutic interaction [ 36 ] and the role of the professional as the expert has particularly potency in minority ethnic communities [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Such factors have been previously identified in different contexts. For example, alternative explanatory processes of stroke and its recovery have been identified in non-Western communities [ 29–32 ], and poor stroke knowledge in minority ethnic groups is a common research finding [ 33–35 ]. Furthermore, it has been suggested that differences in recovery concepts based on cultural understandings may influence the therapeutic interaction [ 36 ] and the role of the professional as the expert has particularly potency in minority ethnic communities [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…As per other developing countries, people with PD in Arab countries may have limited access to resources. In the vast majority of Arab countries, rehabilitation centers for adults with disability are very few and extremely underdeveloped . In particular, multiprofessional rehabilitation centers with specialized trained therapists for people with PD is almost lacking.…”
Section: General Shared Barriers Among Developing Countriesmentioning
confidence: 99%
“…As yet, the custom around the physical contact between men and women in Arabic Islamic countries has its consideration in terms of the access that these women can get out of community rehabilitation services. Community work in Arab countries is restricted to male therapists; this limits therapy for women if available to their homes.…”
Section: Barriers In the Arabian World To Physical Rehabilitation In Pdmentioning
confidence: 99%
“…Stroke patients’ preferences for specific rehabilitation settings have been explored in studies conducted in countries such as Jordan (AL-Oraibi et al 2011 ), the United States (Gregory et al 2010 ) and New Zealand (Hale et al 2003 ). The home was preferred by an overwhelming majority of patients in the US and Jordan studies while no clear preference was established in the New Zealand study.…”
Section: Introductionmentioning
confidence: 99%